*The Effect of a Gross and Fine Motor Intervention Program on Visual-Motor Integration in 4 to 6 Years Old Children - Attieh Miranzadeh Mahabadi; Elahe Erabameri; Fazlolah Bagherzadeh; Davood Homaniyan (University of Tehran, 2021)
Children in preschool are at an optimal time for the development of gross and fine motor skills. Visual-motor integration is an important perceptual-motor skill that children need to acquire in order to function successfully before formal schooling commences. In this study were investigated the effect of three motor intervention programs (gross, fine, & gross-fine)on visual-motor integration in 80 children who presented below average VMI skills scores. From these participants three experimental (n=60)and a control group (n=20)were randomly selected. The experimental groups participated in a 12 week intervention program of three 45 minutes sessions per week. The Beery-Buktenica developmental test of visual-motor integration 6th edition was used to measure the participants VMI skills. Mixed ANOVA with repeated measures and LSD post hoc test was used to analyze effects of motor intervention programs